Results of a Regional Effort to Improve Warfarin Management. (May 2017) - Rose, Adam J.; Park, Angela; Gillespie, Christopher; Van Deusen Lukas, Carol; Ozonoff, Al; Petrakis, Beth Ann; Reisman, Joel I.; Borzecki, Ann M.; Benedict, Ashley J.; Lukesh, William N.; Schmoke, Timothy J.; Jones, Ellen A.; et al.
Background: Improved anticoagulation control with warfarin reduces adverse events and represents a target for quality improvement. No previous study has described an effort to improve anticoagulation control across a health system.Objective: To describe the results of an effort to improve anticoagulation control in the New England region of the Veterans Health Administration (VA).Methods: Our intervention encompassed 8 VA sites managing warfarin for more than 5000 patients in New England (Veterans Integrated Service Network 1 [VISN 1]). We provided sites with a system to measure processes of care, along with targeted audit and feedback. We focused on processes of care associated with site-level anticoagulation control, including prompt follow-up after out-of-range international normalized ratio (INR) values, minimizing loss to follow-up, and use of guideline-concordant INR target ranges. We used a difference-in-differences (DID) model to examine changes in anticoagulation control, measured as percentage time in therapeutic range (TTR), as well as process measures and compared VISN 1 sites with 116 VA sites located outside VISN 1.Results: VISN 1 sites improved on TTR, our main indicator of quality, from 66.4% to 69.2%, whereas sites outside VISN 1 improved from 65.9% to 66.4% (DID 2.3%, P < 0.001). Improvement in TTR correlated strongly with the extent of improvement on process-of-care measures, which varied widely across VISN 1 sites.Conclusions: A regional quality improvement initiative, using performance measurement with audit and feedback, improved TTR by 2.3% more than control sites, which is a clinically important difference. Improving relevant processes of care can improve outcomes for patients receiving warfarin.